Economic Burden Associated with Head Louse (Pediculus humanus capitis) Infestation in Iran - Mojtaba SALIMI; Abedin SAGHAFIPOUR; Hadi HAMIDI PARSA; Majid KHOSRAVI (Tehran University of Medical Sciences, 2020)
Background: The head louse infestation is a public health issue in the world especially, affecting most people who live in camps, school-aged children and their families. Head lice treatment has economic ramifications that often under calculated. The aim of this study was evaluation of economic burden associated with head louse infestation in Iran. Methods: In a cross-sectional study, 500,002 infestations were diagnosed among suspected head lice infested people who referred to health care system in all provinces of Iran during 2017. Direct and indirect costs related to paid by patients and government systems were extracted by referring to accounting documents and interviews with patients and experts and were recorded in researcher-made forms. Microsoft Excel 2010 software was used for economic burden calculation. Results: The incidence rate of head lice infestation in Iran was 500,002/79,926,270 (625.5 per 100,000 populations). Economic burden of head lice in the country was calculated at 5,790,143$. Direct and indirect costs, governmental cost, out of pocket and total costs of head lice were included 3.14$, 2.84$, 5.98$, 5.60$ and 11.58$ per case respectively. Conclusion: The direct and indirect costs associated with treatment of infestations were relatively high. Therefore, the creation of medical facilities such as availability of diagnostic and treatment strategies can be effective in the control of infestation. The adoption of infestation prevention methods, such as health education to people at risk of infestation, reduces the incidence of head lice and imposition of related treatment costs on governmental health care system and head lice cases.